3D Target Localization by Using Particle Filter with Passive Radar Having one Non-cooperative Transmitter and one Receiver - Almanofi, Anas Mahmoud (Array, 2021)
In a passive radar system, localizing a target in Cartesian space is achieved by using one of the following bistatic geometries: multiple non-cooperative transmitters with one receiver, one non-cooperative transmitter with multiple receivers, or one non-cooperative transmitter with one receiver. In this paper, we propose a new method for localizing a target in Cartesian space by passive radar having the bistatic geometry "one non-cooperative transmitter and one receiver". This method depends on using two consecutive particle filters for estimating and analyzing the Doppler frequency and time delay of the target"s echo signal. The theoretical analysis of the proposed method is presented, and its efficiency is verified by simulating the passive radar system with a Digital Video Broadcasting-Terrestrial (DVB-T) transmitter